Neutrophil-to-Lymphocyte Ratios Are Closely Associated With the Severity and Course of Non-mild COVID-19 - Qun, Sen; Wang, Yulan; Chen, Jun; Huang, Xiang; Guo, Hui; Lu, Zhaohui; Wang, Jinquan; Zheng, Changcheng; Ma, Yan; Zhu, Yuyou; Xia, Daqing; Wang, Yinzhong; et al. (Frontiers in Immunology, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is spreading around the world. Measuring the prevention and control of the disease has become the most urgent focus. Objective: Based on coronavirus disease 2019 (COVID-19) clinical data from Wuhan, we conducted an in-depth analysis to clarify some of the pathological mechanisms of the disease and identify simple measures to predict its severity early on. Methods: A total of 230 patients with non-mild COVID-19 were recruited, and information on their clinical characteristics, inflammatory cytokines and T lymphocyte subsets was collected. Risk factors for severity were analysed by binary logistic regression, and the associations of neutrophil-to-lymphocyte ratios (N/LRs) with illness severity, disease course, CT grading, inflammatory cytokines, and T lymphocyte subsets were evaluated. Results: Our results showed that the N/LRs were closely related to interleukin (IL)-6 and IL-10 (P<0.001, P=0.024) and to CD3+ and CD8+ T lymphocytes (P<0.001, P=0.046). In particular, the N/LRs were positively correlated with the severity and course of the disease (P=0.021, P<0.001). Compared to the values at the first test after admission, IL-6 and IL-10 were significantly decreased and increased, respectively, as of the last test before discharge (P=0.006, P<0.001). More importantly, through binary logistic regression, we found that male sex, underlying disease (cardiovascular disease), pulse, and N/LRs were all closely related to the severity of the disease (P=0.004, P=0.012, P=0.013, P=0.028). Conclusions: As a quick and convenient marker of inflammation, N/LRs may predict the disease course and severity level of non-mild COVID-19; male sex, cardiovascular disease, and pulse are also risk factors for the severity of non-mild COVID-19.